2016
DOI: 10.4103/2229-3485.192044
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of serious adverse drug reactions at a tertiary care teaching hospital

Abstract: Objective:The objective of this study was to analyze the various aspects of serious adverse drug reactions (serious ADRs) such as clinical presentation, causality, severity, and preventability occurring in a hospital setting.Materials and Methods:All serious ADRs reported from January 2010 to May 2015 at ADR Monitoring Centre, Department of Pharmacology, B. J. Medical College and Civil Hospital, Ahmedabad, were selected as per the World health Organization –Uppsala Monitoring Center (WHO-UMC) criteria. A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Although majority of the ADRs were nonserious in nature, the common criteria for serious ADRs were initiation or prolongation of hospitalization and required intervention to prevent damage in geriatric and pediatric group, respectively. Similiar observation has been reported by Prajapati et al [ 19 ]…”
Section: Discussionsupporting
confidence: 85%
“…Although majority of the ADRs were nonserious in nature, the common criteria for serious ADRs were initiation or prolongation of hospitalization and required intervention to prevent damage in geriatric and pediatric group, respectively. Similiar observation has been reported by Prajapati et al [ 19 ]…”
Section: Discussionsupporting
confidence: 85%
“…[ 14 ] A study in Ahmedabad, India, reported that an average of 5 drugs per prescription was recommended to patients suffering from serious adverse effects. [ 15 ] From the present study, it was also evident that level of polypharmacy increased with age of the patients. The maximum level of polypharmacy was 5.82 (±0.36) in the age group of 61–70 years.…”
Section: Discussionsupporting
confidence: 65%
“…9,10 Moreover, the drug side effects extend the hospital stay of TB patients and increase the total cost of hospitalization. [11][12][13] The DOTS strategy emphasizes the clinical importance of monitoring AEs during the treatment course in TB patients.…”
Section: Introductionmentioning
confidence: 99%